Blood supply interventions during disasters: efficiency measures and strategies to mitigate volatility - Chua, Geoffrey A. (2022)
In this study, we examine three types of blood supply interventions during disasters; namely, interventions related to recruitment, propensity to donate and retention, and reduction of regeneration time. Through a stylized model, we characterize the equivalence of each of the interventions in meeting blood bank targets while assuming a steady state. We then introduce an effort parameter which determines the difficulty of implementing an intervention and consequently when each should be used. We find that propensity to donate and retention interventions are more effective when donation rate is low, while reduction of regeneration time is an efficient intervention when donation rate is high. However, physiological and ethical limitations mean that the latter can only be used up to a certain degree for intermediate donation rate values depending on the effort parameters. Therefore, recruitment interventions become the preferred intervention by default when donation rate is high. We extend this analysis to a disaster's non-steady state case by using an iterative calculation procedure and show that the equivalence among interventions continue to hold. Further, we devise three strategies that blood banks can use to manage blood donation during disasters: (1) the fixed (2) dynamic, and (3) threshold donation rate strategies. These work on the premise that blood banks have control over the expected number of donations through its use of interventions. By defining what it means to deviate from the steady state, we show that the standard fixed donation rate strategy found in literature leads to increased volatility both during and after disasters. The dynamic donation rate strategy mitigates this volatility but requires daily usage of interventions. This is solved by the threshold donation rate strategy which only uses interventions when the day's donations are expected to deviate from the target. Lastly, we conduct a simulation study using data for two countries and find that the strategies work better for more mature blood banks with higher pre-disaster fill-rates.